Pedagogical Insights into the Perceptions and Attitudes of Pharmacy Students Toward Patient Safety: A Cross-Sectional Study from Pakistan - Samra Bashir; Akash Syed; Maryam Mahmood; Abdul Waheed Khan (Fakultas Tarbiyah Ilmu Keguruan Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2025)
The study evaluated pharmacy students’ perceptions and attitudes toward patient safety at two universities in Islamabad, Pakistan. Final-year Pharm D students completed a 21-item self-administered questionnaire. Data were analyzed using SPSS (version 23.0). The survey had a 97% response rate (160/165 students). Most students (95.7%) believed pharmacists should contribute to patient care, and 69.4% agreed they should report medication errors. Additionally, 87.5% supported incorporating patient safety education in university curricula. However, 63% perceived that competent healthcare professionals don’t make harmful errors, and 50% believed only medical practitioners can identify the cause of errors. Furthermore, 42.5% thought most errors occur due to factors beyond healthcare professionals’ control. The findings indicate that while pharmacy students in Pakistan have positive attitudes toward patient safety, some misconceptions highlight a knowledge gap. Thus, integrating standardized patient safety courses into the pharmacy curriculum is recommended.